Need satisfaction and internet gaming disorder: The mediating role of gaming motivations. - Kong, Jessie Jing Wei; Ng, Phei Yin; Thum, Weng Yew (2023)
A notably higher prevalence of Internet Gaming Disorder (IGD) in Asia is demonstrated by several recent researchers, but still, only limited studies are available on this topic. The present study aimed to explore (1) the predictive effects of need satisfaction (NS) on IGD, (2) the predictive effects of gaming motivation (e.g., intrinsic motivation (IM), extrinsic motivation (EM), and amotivation (AM)) on IGD, and (3) the mediating effects of gaming motivation (e.g., IM, EM, and AM) on the prediction of NS on IGD among multiplayer online battle arena (MOBA) gamers in Malaysia context with Self-Determination Theory (SDT) as theoretical guideline. In general, the current research was a cross-sectional study with a total sample size (N=495) were selected. The participants were recruited by using homogenous purposive sampling method and were given online survey with Internet Gaming Disorder Scale-Short Form (IGDS9-SF), Basic Psychological Need Satisfaction and Frustration Scale (BPNSFS) and Gaming Motivation Scale (GAMS) instruments to fill in. The selected participants met the criteria of (1) MOBA player, (2) at least one-year of MOBA gaming experience, (3) Malaysian, (4) non-professional gamer, (5) age ranging of 18 and 29 years old. Present findings demonstrated that NS, EM, and AM predicted significantly on IGD, while IM predicted IGD non-significantly. On the other hand, all gaming motivations (e.g., IM, EM, and AM) had mediating effects on the prediction of NS on IGD. As a conclusion, current findings had filled in the gap of knowledge relevant to IGD, thus, provided insights to the stakeholders (e.g., policy makers, game developers, and educators) for future interventions.